Gestión de calidad en micro y pequeñas empresas de servicio automotriz ecuatoriano (Tema Central) - Lucero Narváez, Juan Carlos (2020)
The automotive sector is one of the important sectors in Ecuadorian economy, mainly thanks to its contribution in tax collection and in the generation of direct and indirect employment. This sector has a high number of micro and small companies principally dedicated to providing maintenance services. The research is made with the aim of characterizing the quality management carried out by these organizations, which has not been previously analysed, in order to propose a generic quality management model. The research is exploratory-descriptive and is carried out with an interview based qualitative approach, considering a universe of 41 companies that meet the predefined characteristics in a sector in northern Quito, from which a sample of 13 companies was taken. The results allow us to identify shortcomings in the management process, resource management, market understanding, product development, order fulfilment and delivery, customer service, evaluation and improvement. Despite the above, companies do have certain quality practices that are guided by the customer searching, satisfaction and loyalty. Based on this, a general model is proposed, based on the ISO 9001 standard, so that the companies comply with the main conditions of a quality management system.